2015
DOI: 10.12956/tjpd.2015.182
|View full text |Cite
|
Sign up to set email alerts
|

Acute Rheumatıc Fever

Abstract: ve bu hastalığa olan ilgi azalmıştır. Buna rağmen ARA ve romatizmal kalp hastalığı (RKH) ülkemiz dâhil gelişmekte olan ülkelerde önemli bir halk sağlığı problemi olmaya devam etmekte ve güncelliğini korumaktadır. Dünya genelinde edinilmiş kalp hastalıklarının en sık nedeni olan RKH önemli oranda mortalite ve morbiditeye yol açmaktadır (2-6). Tüm dünyada her yıl 10-20 milyon yeni olgunun ortaya çıktığı tahmin edilmektedir (7,8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(92 reference statements)
2
3
0
Order By: Relevance
“…The female-to-male ratio was 1.22. Similar to the literature, the majority of the patients presented in winter (31.3%) and spring (27.5%), when infections are more common [ 18 , 20 25 ]. The literature reports different prevalences for different minor findings such as 54.6–81.1% for arthralgia, 40–62% for fever, 15.9–23% for prolonged PR interval, 81.8–95% for elevated ESR, and 72–81.8% for elevated CRP [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The female-to-male ratio was 1.22. Similar to the literature, the majority of the patients presented in winter (31.3%) and spring (27.5%), when infections are more common [ 18 , 20 25 ]. The literature reports different prevalences for different minor findings such as 54.6–81.1% for arthralgia, 40–62% for fever, 15.9–23% for prolonged PR interval, 81.8–95% for elevated ESR, and 72–81.8% for elevated CRP [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 83%
“…Although rheumatic fever frequently affects patients aged between 5 and 15, studies report ARF attacks in patients aged 2–45 years [ 7 , 18 20 ]. In our study, the mean age of the subjects was 11.7±2.3 years, and 60% were aged 10–13.…”
Section: Discussionmentioning
confidence: 99%
“…Expert agreement has been obtained regarding the idea of subclinical carditis, and ECHO has been widely used in the clinical evaluation of rheumatic carditis, gradually increasing its importance in the diagnosis of ARF over time [2,7,17]. In our study, we found that the prevalence of carditis, especially subclinical carditis, has increased and that these individuals have an increased chance of acquiring permanent rheumatic carditis.…”
Section: Discussionsupporting
confidence: 52%
“…Based on ECHO data, a WHO expert committee accepted previously published criteria for the diagnosis of rheumatic carditis [17]. Those with an ECHO diagnostic of valvular insu ciency but no audible murmur were labeled as having "subclinical" or "silent" carditis.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…In Turkey, ARF is the most common cause of valvular heart disease (36) . In the present study, we preferred to treat patients with carditis showing inflammation with corticosteroids as many physicians have done (37) with the hope of preventing a major cause of morbidity and mortality in the young population.…”
Section: Discussionmentioning
confidence: 99%